Bacterial Diversity and Community Structure in the Pine Wood Nematode Bursaphelenchus xylophilus and B. mucronatus with Different Virulence by High-Throughput Sequencing of the 16S rDNA - Xiang, Yang (PLoS One, 2015)
Bursaphelenchus xylophilus is the pathogen of pine wilt disease. Bursaphelenchus mucronatus is similar to B. xylophilus in morphology. Both species share a common niche, but they are quite different in pathogenicity. Presently, the role of bacteria in pine wilt disease development has been widely speculated. The diversity of bacteria associated with B. xylophilus and B. mucronatus with different virulence remains unclear. In this study, virulence of four B. xylophilus and four B. mucronatus strains were evaluated by inoculating Pinus thunbergii. High-throughput sequencing targeted 16S rDNA of different virulence nematode strains was carried out. The associated bacterial community structures of the eight strains were analyzed. The results showed that 634,051 high-quality sequences were obtained from the eight nematode strains. The number of OTUs of bacteria associated with B. mucronatus was generally greater than those of B. xylophilus. The richness of the community of bacteria associated with high virulent B. xylophilus ZL1 and AmA3 was higher than moderately virulent B. xylophilus AA3, HE2, and all B. mucronatus strains. While the diversity of bacteria associated with B. mucronatus was higher than B. xylophilus. Stenotrophomonas, Pseudomonadaceae_Unclassified or Rhizobiaceae_Unclassified were predominant in the nematode strains with different virulence. Oxalobacteraceae and Achromobacter were found more abundant in the low virulent B. xylophilus and non-virulent B. mucronatus strains.